Lanosterol synthase deficiency promotes tumor progression by orchestrating PDL1‐dependent tumor immunosuppressive microenvironment - Yuan Gao; Kun Zhao; Yulan Huang; Dapeng Zhang; Na Luo; Xiaoqing Peng; Feng Yang; Weidong Xiao; Meng Wang; Rongchen Shi; Hongming Miao (MedComm, 2024)
Abstract Lipid metabolic reprogramming is closely related to tumor progression with the mechanism not fully elucidated. Here, we report the immune‐regulated role of lanosterol synthase (LSS), an essential enzyme in cholesterol synthesis. Database analysis and clinical sample experiments suggest that LSS was lowly expressed in colon and breast cancer tissues, which indicates poor prognosis. The biological activity of tumor cell lines and tumor progression in NOD scid gamma (NSG) mice were not affected after LSS knockdown, whereas LSS deficiency obviously aggravated tumor burden in fully immunized mice. Flow cytometry analysis showed that LSS knockdown significantly promoted the formation of tumor immunosuppressive microenvironment, characterized by the increase in M2 macrophages and polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSCs), as well as the decrease in anti‐tumoral T lymphocytes. With the inhibition of myeloid infiltration or loss function of T lymphocytes, the propulsive effect of LSS knockdown on tumor progression disappeared. Mechanistically, LSS knockdown increased programmed death ligand 1 (PDL1) protein stability by 2,3‐oxidosqualene (OS) binding to PDL1 protein. Anti‐PDL1 therapy abolished LSS deficiency‐induced immunosuppressive microenvironment and cancer progression. In conclusion, our results show that LSS deficiency promotes tumor progression by establishing an OS–PDL1 axis‐dependent immunosuppressive microenvironment, indicative of LSS or OS as a potential hallmark of response to immune checkpoint blockade.